The role of Dialogue Leadership In promoting job embeddedness: Analytical study of a sample of private schools in Baghdad city - Abed Aubed, Hayder; Abbas Abod, Rasha (Iraqi Journal for Administrative Sciences, 2024)
The present study aims to clarify the role of the dialogue leadership represented by its dimensions (listening - respecting - suspending - voicing) in promoting job Embeddedness in its dimensions (fit -links - Sacrifice) at the level of the organization and society. For a sample of teaching staff for a group of private schools in Baghdad city on both sides of Karkh and Rusafa. The descriptive analytical method was used in collecting and interpreting information, the study sample reached (196) individuals. The researcher used the questionnaire form in the process of data collection. The naturalness, confirmatory constructive validity, a set of appropriate descriptive statistics, the correlation coefficient (Pearson), and the method (SEM modelling) to measure the effect relationship between the study variables, and these methods were used on the analysis programs ((Amos.V.23, SPSS. V 23, Microsoft Excel)), The researcher came to a set of conclusions, the most important of which is the existence of a direct correlation between the variables of the study, and the existence of a positive effect of the dimensions of the Dialogue leadership in promotion job Embeddedness, and based on these conclusions the researcher presented a set of recommendations.